Coping with Stressful Behaviour of Autism: Voices of Lusaka Parents, Zambia - Chalwe, Hellen Kalumba; Muzata, kenneth; Mandyata, Joseph M (MASI Mandiri Edukasi, 2024)
This was a hermeneutical phenomenological qualitative study of the coping strategies parents of children with autism spectrum disorder (ASD) use to cope with the demanding behaviours of their children in the Lusaka district – in Zambia. Parents, as key caregivers of children with disabilities, are likelier to develop unhappiness and worry than parents of classically developing children. Parental stress is usually associated with the severity of the ASD disorder. It was imperative to study how parents in Lusaka District coped with children with ASD daily. Interviews were used to collect data. Ten (10) parents of children with ASD were purposively selected to participate in the study. Data analysis was done in themes that revealed extra worries for parents, caused mainly by a lack of information about ASD, especially before diagnosis. Parents adopted specific strategies to cope with their children's problematic behaviour in areas of social interaction. Further, parents require much assistance developing interaction between them and specialists to acquire support services regarding coping strategies for their children's behaviour